Homogenization of Electrostatic Problems in Nonlinear Medium with Thin Perfectly Conducting Grids - Goncharenko, M. V.; Prytula, V. I. (Журнал математичної фізики, аналізу, геометрії, 2006)
The asymptotic behavior of solutions of the family of nonlinear elliptic equations in domains with thin grids concentrating near a hypersurface when measure of the wires tends to zero and the density tends to infinity is investigated. The homogenized equations and the homogenized boundary conditions are derived. The homogenization technique is based on applying of the abstract theorem on homogenization of the nonlinear variational functionals in the Sobolev-Orlicz spaces. Mathematics Subject Classification: 35B27.